Finite and infinite system gamma ray buildup factor calculations with detailed physics. (November 2015) - Atak, Haluk; Çelikten, Osman Şahin; Tombakoğlu, Mehmet
Abstract: Examination of physical interactions of photons in materials is a significant subject for buildup factor studies. In most of the buildup calculations, by default, coherent (Rayleigh) scattering is ignored and the Compton scattering is modeled by free-electron Klein–Nishina formula with "simple physics" treatment. In this work, photon buildup factors are calculated for many different cases including "detailed physics" by taking into account coherent and bound-electron Compton scatterings with the Monte Carlo code, MCNP5, and the results are compared with the literature values. They are computed for point isotropic photon sources up to depths of 20 mean free paths and at the three photon energies most widely used (0.06, 0.6 and 6 MeV). Calculations are made for both finite and infinite homogeneous ordinary water media. It is concluded that Coherent scattering is very dominant at low energies and for deep penetrations and assumed physical approximation (simple/detailed, finite/infinite) is the critical point for determining shielding material dimensions. After all, it can be stated that all parametric assumptions should be clearly given and indicated in the tabulation of photon buildup factors. Abstract : Highlights: Gamma ray buildup factors have been generated both for finite and infinite ordinary water systems. The importance of detailed physics calculations is emphasized for low energy gamma rays. Results of finite and infinite calculations are compared.